Population Density on Types of Waste Disposal in Malang City - Lirofiatillah, Lirofiatillah; Lestari, Rina Fiji; Hartono, Sugi; Sueb, Sueb (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2018)
The population growth in Indonesia experiencing a very high development, causing population density. This study aims to know about environmental conditions, the density of population and waste disposal in Malang city and effect between population density and types of landfills. The method was an observational study using observation, questionnaire and closed interview guidelines. The results of this study were (1) the environmental conditions categorized good, (2) the average population density is 175,814 people per square km, (3) 63.33% respondents road throw domestic waste and not processed. (4) the population density variable does not influence the type of waste disposal.